Consumers' Willingness to Pay for Agri-Food Products Delivered with Electric Vehicles in the Short Supply Chains. Issue 2 (June 2023) - Galati, Antonino; Migliore, Giuseppina; Thrassou, Alkis; Schifani, Giorgio; Rizzo, Giuseppina; Adamashvili, Nino; Crescimanno, Maria
This study aims at investigating the consumers' willingness to pay (WTP) for agri-food products delivered in the farmers markets with electric vehicles (EVs). The empirical analysis has been carried out by administering an online questionnaire to 273 consumers within a hypothetical context. A multiple price list has been provided in order to measure the price premium for 1 kg of oranges transported by EVs comparing with the ones transported by traditional vehicles. A Tobit regression model has been used for the data analysis in order to identify the most influential factors affecting the consumers' WTP. Results suggest that consumers' WTP is mainly influenced by environmental attitudes, knowledge and possibility of engaging in responsible purchasing, and the approval of friends and relatives (social norms). This study delivers insights into support both farmers' choice to invest in EVs and policymakers to develop policies promoting this transition process. The main limitations of this study are related to the use of a random sample of respondents and to the social desirability bias linked to self-reported questions.